Strategi Pelestarian Cagar Budaya Gereja St. Antonius Padova Sebagai Daya Tarik Wisata Kota Pasuruan - Ngefak, Kerenhapuk Murike; Titasari, Coleta Palupi; Kristiawan, Kristiawan (Humanis; Vol 27 No 4 (2023)DO - 10.24843/JH.2023.v27.i04.p09, 2023)
Historic buildings that have a colonial style can become an element of tourism development in Pasuruan, including the uniqueness of the local character can be enjoyed as the memories of the past as a tourist attraction. Based on the current conditions, it is necessary to conduct a research related to the directions for the preservation of St. Anthony Padova Church as a Culture Heritage and precisely to maintain the identity and characteristic of the building. Therefore, this study aims to formulate efforts to preserve the cultural heritage of the building, which has historical value as a tourist attraction destination. St. Anthony Padova Church has the potential and deserves to be utilized as one of tourism destination. Utilization of the Cultural Heritage Building of the Church of St. Antonius Padova as a tourist attraction must be directed to the superiority and uniqueness of the building